Developing a new line of patter: can doctors change their consultations for sore throat? - Rollnick, S; Seale, C; Kinnersley, P; Rees, M; Butler, C; Hood, K (2002)
BACKGROUND AND OBJECTIVES: Doctors report pressure from peers to reduce prescribing of antibiotics for minor respiratory illnesses, and from patients to do the opposite. It has been suggested that doctors adopt a more patient-centred consulting style in order to encourage patient satisfaction and shared decision-making. No evidence exists that such changes are achievable. We developed a new, on-site method for training postgraduates and used this for teaching patient-centred intervention. Here, we examine whether this training method is associated with changes in consulting patterns in consultations for sore throat with children, among doctors from a single group practice. METHODS: Audiotaped consultations (simulated and real) conducted before and after training were analysed and interviews were carried out with participants about the impact of training. SETTING: A general practice in South Wales. PARTICIPANTS: Four general practitioners who consulted with 25 real and simulated patients participated in the study. MAIN OUTCOME MEASURES: Four patient-centred skills used by doctors and 2 patient behaviours measured before and after training were identified. RESULTS: Three out of 4 practitioners produced clear evidence of changes in patient-centred consulting skills. These changes were evident in simulated and real consultations 2 and 4 weeks later, respectively. Prior to training the doctors produced only five examples of patient-centred skills in 10 consultations. After training they produced 39 examples in 15 consultations. CONCLUSIONS: Evidence from both consultations and interviews indicated that the intervention and training were well received and had been put into practice.